The role of social and political factors in the success of rewilding projects - Weber Hertel, Sarah; Luther, David (Frontiers in Conservation Science, 2023)
The ecological aspects behind the success and failure of rewilding projects have been looked at in literature and case studies, but rarely have sociopolitical factors been included in these classifications. To truly determine which factors lead to success in rewilding projects, inclusive of sociopolitical factors, we created global models that analyze 120 case studies from IUCN's "Global Re-introduction Perspectives" that fit under IUCN's definition of rewilding. Models included the ten guiding principles for rewilding from IUCN's Rewilding Thematic Group, success factors, and threats to success as defined from existing literature. We measured the selfreported "level of success" from the case report examples against the guiding principles, success factors and threats to determine which were more likely to be associated with successful rewilding projects. Local awareness of the benefits of rewilding and illustrating a proof of concept of rewilding were the factors that were most strongly associated with higher levels of success in rewilding projects, as self-reported by case report authors, as well as Guiding Principle 9 "rewilding recognizes the intrinsic value of all species". Our results indicate that both ecological and sociopolitical factors are critical to successful rewilding projects and both need to be accounted for and included in future planning of rewilding projects to maximize the possibility of successful rewilding.